2008
DOI: 10.4049/jimmunol.180.5.2886
|View full text |Cite
|
Sign up to set email alerts
|

The Role for Monocyte Chemoattractant Protein-1 in the Generation and Function of Memory CD8+ T Cells

Abstract: Memory T cells are resistant to the conventional costimulatory blockade and therefore impede tolerance induction. However, their migratory, survival, and functional requirements for chemokines are not well understood. We herein examine the role for MCP-1 or CCL2 in the generation, migration, and function of memory CD8+ T cells. We found that overall generation of both central memory (TCM) and effector memory (TEM) CD8+ T cells was severely impaired in the absence of MCP-1. Importantly, the survival of TEM, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 59 publications
1
30
1
Order By: Relevance
“…The relative resistance of the CCR5 + CCR2 + cells to death was associated with high levels of BCL-2 and cFLIP, antiapoptotic proteins within the intrinsic (cytokine withdrawal) and extrinsic (Fas-or TCR-mediated) pathways, respectively. It is of interest that CCL2/MCP-1 has been reported to protect activated mouse CD8 + T cells from death due to cytokine withdrawal (76) and to be important for survival of CD8 + T EM in mice (77). However, in our assays of spontaneous and FASmediated death, we saw no protective effect of adding CCL2/MCP-1 (data not shown).…”
Section: Ccr2contrasting
confidence: 53%
“…The relative resistance of the CCR5 + CCR2 + cells to death was associated with high levels of BCL-2 and cFLIP, antiapoptotic proteins within the intrinsic (cytokine withdrawal) and extrinsic (Fas-or TCR-mediated) pathways, respectively. It is of interest that CCL2/MCP-1 has been reported to protect activated mouse CD8 + T cells from death due to cytokine withdrawal (76) and to be important for survival of CD8 + T EM in mice (77). However, in our assays of spontaneous and FASmediated death, we saw no protective effect of adding CCL2/MCP-1 (data not shown).…”
Section: Ccr2contrasting
confidence: 53%
“…These data suggested that trophoblasts and monocytes were likely to be involved in the generation of CD45RO + T cells. The secretion of MCP-1 was determined by ELISA, as it has been demonstrated to be significant in the generation of CD45RO + T cells (16). Consistent with a previous study (15), we observed that the production of MCP-1 in the MHM was notably higher than that in the monocyte or human trophoblast HTR8/SVneo cell line cultures (Fig.…”
supporting
confidence: 79%
“…It has been demonstrated that the interaction of trophoblast cells and monocytes markedly enhances the expression of cytokines/chemokines, including MCP-1 (15). MCP-1, the main monocyte chemoattractant, has been demonstrated to be associated with the generation and survival of CD45RO + T cells (16). In the present study, to investigate the possible expansion and activation mechanisms of decidual CD45RO + T cells, we developed an effective in vitro model to generate these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of chemokines such as CCL5, CXCL8, and CXCL10 in the pathogenesis of lung cancer, and in other cancers, has been increasingly appreciated (27,28). However, the role of other important chemokines in lung cancer, such as CCL2, remains unclear.…”
Section: Discussionmentioning
confidence: 99%